The Impact of Zakat Fund Distribution on BAZNAS Cendekia School (SCB): A Sustainability Livelihood Assessment - Wibowo, Herry; Rachmad, Dedy; Indra, Indra (Center of Strategic Studies (PUSKAS) BAZNAS, 2024)
This research aims to measure the extent of the impact of the Zakat distribution program in the education sector by taking a case study of the BAZNAS Cendekia School (SCB) program. This research was conducted using an evaluative approach with the Sustainability Livelihood Impact Assessment (SLIA) framework. Data collection was carried out through literature study, field observations, in-depth interviews. The sample population for this research was comprehensive (total sampling) consisting of 21 school management people, 26 teaching staff, 277 students and 30 heads of local families. The findings from this research show that there has been an increase in all aspects of SLIA with various scales of change, namely the human resource capital aspect of 0.30, social capital of 0.25, natural resource capital of 0.30, physical capital of 0.25 and financial capital of 0.41. The highest change occurred in the financial capital aspect of 0.41 and the lowest change occurred in the social and physical capital aspect. This shows that during the 2017-2020 period, the current social and financial modalities are aspects that are felt to be very useful at this time, so in the future the minimum contribution achieved in this aspect can be maintained. Meanwhile, regarding the aspects of human resource, natural resources and physical modalities, these three aspects need to receive attention to improve optimization so that these already good assets can be more optimally useful for all parties who have an interest in the sustainability of SCB for better education. A limitation of this research is the unavailability of baseline data to measure how big the stakeholder and beneficiary perception scores were at the start of the program. Because this research was conducted in the 3rd year after the SCB started, of course the perception comparison between then and now has the potential for quite large bias.